The effect of the maintaining the ball possession on the intensity of games - Felipe Lovaglio Belozo; Eliel Calazans Ferreira; Cristian J. R. Lizana; Guilherme Grandim; João Claudio Machado; René Brenzikofer; Denise Vaz Macedo; Milton Shoiti Misuta; Alcides José Scaglia (Universidade Estadual Paulista (UNESP), 2016)
Abstract The use of small-sided games (SSG) for soccer training has increased considerably in recent years. Tactical principles can influence the intensity and the movement of soccer players during training. The aim of this study was to evaluate the influence of maintaining possession of the ball on the intensity and the time of motion characteristics of players during training in games. Eleven athletes of the U-20 category of a professional club in São Paulo, Brazil, participated in this study. To check the influence of the tactical principle, we used a game control and an experimental game in three different field dimensions and number of players. The results show that possession of the maintenance rule influences the intensity of the games (p <0.05). However, it is concluded that the rule is fundamental for training through games.